Scientific Opinion on Flavouring Group Evaluation 201 Revision 2 (FGE.201Rev2): 2‐alkylated, aliphatic, acyclic alpha, beta‐unsaturated aldehydes and precursors, with or without additional double‐bonds, from chemical subgroup 1.1.2 of FGE.19. (17th October 2018) - ,; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Engel, Karl‐Heinz; Fowler, Paul; Frutos Fernandez, Maria Jose; Fürst, Peter; Gundert‐Remy, Ursula; Husøy, Trine; Mennes, Wim; Moldeus, Peter; et al.
Abstract: The Panel on Food Additives and Flavourings of the European Food Safety Authority was requested to consider in this revision 2 of Flavouring Group Evaluation 201, the additional data on genotoxicity submitted by the Industry on two substances, 2‐methylpent‐2‐enal [FL‐no: 05.090] and 2 methylcrotonaldehyde [FL‐no: 05.095], from subgroup 1.1.2 of FGE.19. In FGE.201Rev1, the Panel concluded that further data were required in order to clarify the genotoxic potential of this subgroup and considered the testing of 2‐methylcrotonaldehyde [FL‐no: 05.095] in a comet assay in liver and duodenum, the first site of contact, as a preferred option to further investigate the genotoxicity in vivo . New genotoxicity studies have been submitted for both 2‐methylpent‐2‐enal [FL‐no: 05.090] and 2‐methylcrotonaldehyde [FL‐no: 05.095]. 2‐Methylpent‐2‐enal [FL‐no: 05.090] tested in a combined micronucleus/comet assay did not induce DNA damage, overruling the weak gene mutation effect observed in bacteria and confirming the negative results observed in the in vitro micronucleus assay. 2‐Methylcrotonaldehyde [FL‐no: 05.095] did not induce gene mutations in liver and glandular stomach of transgenic rats. In addition, 2‐methylcrotonaldehyde [FL‐no: 05.095] tested in an in vivo comet assay in liver and duodenum, it did not induce DNA damage. Overall, the Panel concluded that the genotoxic evidence observed in vitro, was not confirmed in vivo for the representative substances 2‐methylcrotonaldehyde [FL‐no: 05.095] and 2‐methylpent‐2‐enal [FL‐no: 05.090], therefore all the 10 substances in this subgroup [FL‐no: 02.174, 05.033, 05.090, 05.095, 05.105, 05.107, 05.126, 07.261, 12.065 and 12.079] can be evaluated through the Procedure for the evaluation of flavouring substances.